PROFESSIONAL COMPETENCE OF FUTURE ENGINEERS IN THE PROCESS OF TRAINING OF COMPUTER SCIENCE DISCIPLINES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The theoretical principles of formation professional competences of future engineers are presented by means of informatics disciplines in this article. The issue of reforming of the higher system of education in Ukraine is considered by introducing a competent approach to the organization of the educational process. The role of teaching computer science disciplines is determined in the formation of professional competencies of future engineers, psychological and pedagogical background and methodical requirements as for the design of competence-oriented content of training of the informational disciplines of future engineers. The article reveals the ways of practical implementation of the competence approach during the training of the computer science disciplines by future engineers and describes the developed model of formation of professional competencies of future engineers in the process of studying computer science disciplines. The peculiarities of forming professional competencies are determined during classroom sessions. The means of development of professional competencies and formation of research skills of future engineers are revealed by means of the using of competence-oriented tasks in students' independent work and methodical peculiarities of organization of educational computer-technology practice in the context of implementation of the competence approach. The experimental review of the effectiveness of the developed model is described as for the formation of professional competencies of future engineers in the process of training computer science disciplines.